2016
DOI: 10.1093/jrr/rrw029
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy for patients with oligometastases from colorectal cancer: risk-adapted dose prescription with a maximum dose of 83–100 Gy in five fractions

Abstract: We previously reported that the local control of pulmonary metastases from colorectal cancer (CRC) following stereotactic body radiotherapy (SBRT) with moderate prescription dose was relatively worse. We investigated the treatment outcomes and toxicities of patients with oligometastases from CRC treated by SBRT using risk-adapted, very high- and convergent-dose regimens. Among patients referred for SBRT from August 2011 to January 2015, those patients were extracted who had liver or pulmonary metastases from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…Hypofractionated radiotherapy at higher doses per fraction may increase radiation-induced damages due to direct cytotoxicity, and may lead to microvascular disruption (38)(39)(40)(41). It was suggested that liver metastases should be treated by ablative SBRT as often as possible, and the present data support the findings reported in previous studies (15,16). In the present study, adding margins >8 mm to the ITV led to improved outcomes, although the differences were not significant.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Hypofractionated radiotherapy at higher doses per fraction may increase radiation-induced damages due to direct cytotoxicity, and may lead to microvascular disruption (38)(39)(40)(41). It was suggested that liver metastases should be treated by ablative SBRT as often as possible, and the present data support the findings reported in previous studies (15,16). In the present study, adding margins >8 mm to the ITV led to improved outcomes, although the differences were not significant.…”
Section: Discussionsupporting
confidence: 87%
“…However, the resection rate of hepatic metastases has been reported to be only 0.8-22% (25). Liver metastases are known to have different sensitivities to radiation therapy based on the location of the primary tumor; it has been reported that liver metastases derived from CRCs were significantly more resistant to radiation compared with liver metastases derived from non-colorectal cancers (15)(16)(17). Thus, patients with CRC metastases may benefit from dose escalation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment alternatives for patients unsuitable for surgery are limited. Stereotactic body radiation therapy (SBRT) has recently been added to the treatment armamentarium of CRC lung metastases . Although RFA has been used as a treatment alternative for pulmonary oligometastases, this approach has fundamental limitations due to lung tissue properties.…”
Section: Discussionmentioning
confidence: 99%